The effect of hospital-acquired infection with Clostridium difficile on length of stay in hospital - Forster, Alan J. (Canadian Medical Association, 2012)
BACKGROUND: The effect of hospital-acquired infection with Clostridium difficile on length of stay in hospital is not yet fully understood. We determined the independent impact of hospital-acquired infection with C. difficile on length of stay in hospital. METHODS: We conducted a retrospective observational cohort study of admissions to hospital between July 1, 2002, and Mar. 31, 2009, at a single academic hospital. We measured the association between infection with hospital-acquired C. difficile and time to discharge from hospital using Kaplan–Meier methods and a Cox multivariable proportional hazards regression model. We controlled for baseline risk of death and accounted for C. difficile as a time-varying effect. RESULTS: Hospital-acquired infection with C. difficile was identified in 1393 of 136 877 admissions to hospital (overall risk 1.02%, 95% confidence interval [CI] 0.97%–1.06%). The crude median length of stay in hospital was greater for patients with hospital-acquired C. difficile (34 d) than for those without C. difficile (8 d). Survival analysis showed that hospital-acquired infection with C. difficile increased the median length of stay in hospital by six days. In adjusted analyses, hospital-acquired C. difficile was significantly associated with time to discharge, modified by baseline risk of death and time to acquisition of C. difficile. The hazard ratio for discharge by day 7 among patients with hospital-acquired C. difficile was 0.55 (95% CI 0.39–0.70) for patients in the lowest decile of baseline risk of death and 0.45 (95% CI 0.32–0.58) for those in the highest decile; for discharge by day 28, the corresponding hazard ratios were 0.74 (95% CI 0.60–0.87) and 0.61 (95% CI 0.53–0.68). INTERPRETATION: Hospital-acquired infection with C. difficile significantly prolonged length of stay in hospital independent of baseline risk of death.